Conservation of structural fluctuations in homologous protein kinases and its implications on functional sites. Issue 7 (21st April 2016) - Kalaivani, Raju; de Brevern, Alexandre G.; Srinivasan, Narayanaswamy
ABSTRACT: Our aim is to explore the similarities in structural fluctuations of homologous kinases. Gaussian Network Model based Normal Mode Analysis was performed on 73 active conformation structures in Ser/Thr/Tyr kinase superfamily. Categories of kinases with progressive evolutionary divergence, viz. (i) Same kinase with many crystal structures, (ii) Within‐Subfamily, (iii) Within‐Family, (iv) Within‐Group, and (v) Across‐Group, were analyzed. We identified a flexibility signature conserved in all kinases involving residues in and around the catalytic loop with consistent low‐magnitude fluctuations. However, the overall structural fluctuation profiles are conserved better in closely related kinases (Within‐Subfamily and Within‐family) than in distant ones (Within‐Group and Across‐Group). A substantial 65.4% of variation in flexibility was not accounted by variation in sequences or structures. Interestingly, we identified substructural residue‐wise fluctuation patterns characteristic of kinases of different categories. Specifically, we recognized statistically significant fluctuations unique to families of protein kinase A, cyclin‐dependent kinases, and nonreceptor tyrosine kinases. These fluctuation signatures localized to sites known to participate in protein‐protein interactions typical of these kinase families. We report for the first time that residues characterized by fluctuations unique to the group/family are involved in interactions specific to the group/family. As highlighted for Src family, local regions with differential fluctuations are proposed as attractive targets for drug design. Overall, our study underscores the importance of consideration of fluctuations, over and above sequence and structural features, in understanding the roles of sites characteristic of kinases. Proteins 2016; 84:957–978. © 2016 Wiley Periodicals, Inc.